Narcissism in the workplace research, opinion and practice - DuBrin, Andrew J. (Cheltenham Edward Elgar, 2012)
My coworker was a narcissist. I had never encountered this kind of individual before and was unprepared for the experience that would forever change my view of the workplace. The same was true of my boss, and dealing with a narcissist provided both of us with a most unfortunate lesson in leadership.
Includes bibliographical references and index.
Keywords: Employees--Attitudes